Tanggung Jawab Hukum Penyelenggara Program Makan Bergizi Gratis terhadap Penerima Manfaat Pihak Ketiga dalam Insiden Keracunan Massal - Tegar Raffi Putra Jumantoro; Ermanto Fahamsyah (Research and Development Agency Ministry of Home Affairs, 2026)
This study analyzes the legal responsibility of organizers of the Free Nutritious Meal (MBG) program in Indonesia following nationwide mass poisoning incidents subsequent to its 2025 rollout. It examines weaknesses in food safety oversight, operational compliance, and access to remedies for affected students who lack direct contractual relations with implementing entities. The study aims to determine whether students qualify as intended third-party beneficiaries and to identify the civil liability applicable to the National Nutrition Agency (BGN) and its implementing units. This study employs a normative legal research method using deductive reasoning and combines statutory analysis with literature review. Sources include legislation, academic literature, incident reports, laboratory findings, and program documents collected through systematic library research. The analysis connects legal provisions with empirical evidence to assess coherence between law in books and law in action and to identify normative gaps. The findings indicate that students affected by MBG-related food poisoning incidents may be recognized as intended third-party beneficiaries under Article 1317 of the Civil Code and related constitutional and food safety norms. However, Presidential Regulation No. 115 of 2025 is primarily administrative and lacks explicit provisions on liability attribution compensation mechanisms insurance obligations and mandatory recall procedures. The study concludes that the recognition of beneficiary status must be accompanied by regulatory reform and institutional redesign. It recommends revising Presidential Regulation No. 115 of 2025 to define civil liability rules require compulsory liability insurance create a temporary compensation fund and establish a centralized response and compensation unit to expedite access to remedies.